Crystal facet engineering of ZnO photoanode for the higher water splitting efficiency with proton transferable nafion film. (February 2016) - Pawar, Amol U.; Kim, Chang Woo; Kang, Myung Jong; Kang, Young Soo
Abstract: Zinc oxide (ZnO) is considered as an extraordinary photoanode with direct band gap and high charge mobility for solar light water splitting reaction, but it suffers from proton (H + ) produced by the photo-oxidation reaction. In the current work, we demonstrate that the long term-stability of ZnO photoanode with the introduction of proton transfer media. Proton transferable polymer such as nafion allows favorable transport of the generated H + ions from the surface of ZnO photoanode to electrolyte and results in an enhanced its stability. Nafion polymer film was coated on the surface of ZnO thin film photoanode with each selectively exposed (002), (100) and (101) facet. Especially, nafion film with (002) crystal facet ZnO photoanode showed 3.9 mA/cm 2 of the high photocurrent density and 0.3–0.6 μmol/cm 2 of high oxygen and hydrogen gas evolution for 2 h. The photoelectrochemical performance of nafion coated (002), (100) and (101) facet oriented ZnO thin film photoanode increase the performance of water splitting reaction and stability of ZnO thin film were demonstrated as a development of high efficient ZnO photoelectrode. Present work suggests the strategy to fabricate the stable metal oxide photoelectrode with the high photoelectrochemical performance. Highlights: ZnO photoanode with different facets shows different photocatalytic performance. A (002) facet orientated ZnO photoanode shows better water splitting activity. Nafion will help to relocate H + ions and improve stability of ZnO thin film.